Whole-genome sequencing analysis of Staphylococcus aureus isolated from female patients with mastitis in Henan, China - Yu, Jing; Ding, Yanzi; Zhang, Xue; Fang, Yang; Tai, Shuhong; Yuan, Enwu; Duan, Yitao (Journal of Global Antimicrobial Resistance, 2025)
•Three clonal lineages (ST22, ST59, and ST398), which account for 70.9% of all strains, play an important role in mastitis in lactating women.•Mastitis-associated Staphylococcus aureus ST22-t309 was the main prevalent lineage of MSSA, while ST59-t437 was the main prevalent lineage of MRSA.•Mastitis-associated Staphylococcus aureus expresses multiple virulence genes, and ST22, ST398, and ST59 demonstrate different virulence patterns. To study the molecular characteristics, antibiotic resistance profiles and virulence features of Staphylococcus aureus (SA) isolates that cause mastitis. 117 SA isolates were collected from women with mastitis. Strain identification and antimicrobial susceptibility testing were conducted using the Vitek 2 system. All SA isolates were sequenced on the Illumina HiSeq platform. Multilocus sequence typing (MLST), ResFinder, BLAST against virulence factors, spaTyper, and SCCmecFinder were employed to analyse the strains. 35 methicillin-resistant Staphylococcus aureus (MRSA) strains and 82 methicillin-sensitive Staphylococcus aureus (MSSA) strains were isolated from women with acute breast abscesses. The rates of resistance to various antibiotics were significantly higher among MRSA isolates than among MSSA isolates. 22 sequence types (STs), 35 staphylococcal protein A (spa) types, and 4 SCCmec types were identified. ST22, ST59, and ST398 were the major lineages, and t309 and t437 were the most common spa types. SCCmec-IVa was the predominant SCCmec type. Interestingly, toxin gene subtypes A (hlgA, hlgB, hlgC, lukF-PV, lukS-PV, seg, sei, sem, sen, seo, seu, n = 54), B (hlgA, hlgB, hlgC, seb, sek, seq, n = 13), C (hlgA, hlgB, hlgC, lukD, lukE, n = 10), and D (hlgA, hlgB, hlgC, n = 10) accounted for 74.4% (87/117) of all SA isolates, suggesting the high expression of virulence genes. ST22, ST398, and ST59 are the main types that cause mastitis and have different virulence factor profiles. This study provides deeper insights into the molecular epidemiology of SA associated with acute mastitis.